In vitro Anti-influenza Activity of in silico Repurposed Candidate Drug Cycrimine. Issue 8 (November 2019) - Matejin, Stanislava; Bukreyeva, Natalya; Radosevic, Draginja; Sencanski, Milan; Mantlo, Emily; Veljkovic, Veljko; Glisic, Sanja; Paessler, Slobodan
Background: Due to the limitations of current antiviral therapies because of drug resistance and the emergence of new circulating viral strains, novel effective antivirals are urgently needed. Results of the previous drug repurposing by virtual screening of DrugBank revealed the anticholinergic drug cycrimine as a possible inhibitor of the influenza virus infection. Methods: In this study we examined the potential antiviral activity of cycrimine in vitro . Results: The experimental results showed the anti-influenza activity of cycrimine against two different influenza A subtypes in cell culture. Conclusions: The findings of this study suggest cycrimine as a potential therapeutic agent for influenza.